Examining the relationship of a survey based measure of math creativity with math achievement: Cross-national evidence from PISA 2012. (2016) - Sebastian, James; Huang, Haigen
Highlights: A survey based measure for math-creativity from the PISA 2012 student questionnaire is proposed. Math-creativity is found to be positively related to achievement at the student level. At the country level average math-creativity is found to be negatively related to average math performance. Abstract: Developing creative thinking skills in school children has become an important topic of discussion for education research and policy. International assessments of students' academic learning skills have started to consider students' creative thinking and problem solving skills along with assessments of traditional academic subjects. In this study we use the Program for International Student Assessment (PISA) 2012 data to propose a survey based measure of math-creative thinking skills and further examine its relationship to math achievement. The results show that within schools, at the student-level, math-creativity is positively related to student achievement. Between countries, average math performance is negatively related to average math-creativity skills. Many countries that performed poorly on the 2012 math assessment have relatively higher proportions of students who consider themselves open problem solvers. Our findings highlight the importance of considering level of analysis when examining the relationship of creativity with achievement.